Magnesium-derived sea surface temperature reconstruction (1449 to 2013 CE) from a Bermudan stalagmite - Forman, Edward C G; Baldini, J U L; Jamieson, Robert A; Lechleitner, Franziska A; Walczak, Izabela W; Nita, Dan C; Smith, Struan R; Richards, David A; Baldini, Lisa M; McIntyre, Cameron; Müller, Wolfgang; Peters, Andrew J (PANGAEA, 2025)
The BER-SWI-13 stalagmite was collected March 2013 from Leamington Cave, Bermuda, and had an active drip rate that was responsive to rain events. Sixteen U-Th dates were obtained but not used in the chronology owing to the unjustifiably high growth rate variability they imply. Twenty-five 8-9 mg carbonate powder samples were taken for radiocarbon analysis, and an 'average' chronological model following Fohlmeister & Lechleitner (2019; doi:10.1016/j.quageo.2019.02.008). Trace element concentrations were measured and standardised using NIST 610/612. Magnesium concentrations exhibit well-developed annual cyclicity throughout most of the record. The chronology is thus derived from a magnesium cycle count which is modelled to a radiocarbon age model. The final chronology spans 1449 to 2013 CE and the resultant Mg record an average of 32.8 datapoints a year. This Mg record was smoothed using a Savitzky-Golay filter to remove the influence of weather extrema and resampled to monthly spacing. The monthly Mg record was converted to sea surface temperature (SST) by calibrating it to the coral record presented in Goodkin et al. (2008; doi:10.1029/2007PA001532). The BER-SWI-13 SST record shows evidence of Gulf Stream positional migration starting in around 1720 CE.
Keywords: magnesium; palaeoclimate reconstruction; Sea surface temperature; SST; stalagmite; stalagmites